Optimization of purification and refolding of the human chemokine receptor CXCR1 improves the stability of proteoliposomes for structure determination - Park, Sang Ho; Casagrande, Fabio; Chu, Mignon; Maier, Klaus; Kiefer, Hans; Opella, Stanley J. (Biochimica et biophysica acta, 2012)
The human chemokine receptor CXCR1 is a G-protein coupled receptor that has been successfully expressed in E. coli as inclusion bodies, and purified and refolded in multi-milligram quantities required for structural studies. Expression in E. coli enables selective and uniform isotopic labeling with 13C and 15N for NMR studies. Long-term chemical and conformational stability and oligomeric homogeneity of CXCR1 in phospholipid bilayers are crucial for structural studies under physiological conditions. Here we describe substantial refinements in our previously described purification and reconstitution procedures for CXCR1 in phospholipid bilayers. These refinements have led to the preparation of highly purified, completely monomeric, proteoliposome samples that are stable for months at 35°C while subject to the high power radiofrequency irradiations of solid-state NMR experiments. The principal changes from the previously described methods include: 1) ensure that CXCR1 is pure and homogeneously monomeric within the limits of detection (>98%); 2) monitor and control the pH at all times especially following the addition of TCEP, which serves as a reducing agent but also changes the pH; 3) slowly refold CXCR1 with the complete removal of all traces of SDS using a KCl precipitation/dialysis method; and 4) ensure that the molar ratio between the CXCR1 and the phospholipids does not change during refolding and detergent removal. NMR samples prepared with these protocols yield reproducible results over a period of many months at 35°C. This purification and refolding protocol is likely to be applicable with minimal changes to other GPCRs as well as other membrane proteins. ► It is possible to purify CXCR1 as homogeneous monomers. ► 7mg of pure CXCR1 is obtained from 1L culture. ► Isotopically labeled CXCR1 is stable for more than 6months.